PENERAPAN ANGGARAN FLEKSIBEL SEBAGAI ALAT PENGENDALI BIAYA OVERHEAD PABRIK (Studi Kasus pada PG. MERITJAN Kediri) - Riana, Riana; Ratih, Nur Rahmanti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2016)
Adoption of Flexible budget as a means of controlling overhead costs (Case Study on PG. Meritjan Kediri ) aims to control overhead costs by implementing flexible budget at PG.Meritjan Kediri. Data Analysist techniques used in this research is quantitative descriptive by using a factory overhead cost variance analysis. From the analysis of direct labor hours show that there is not efficient in the analysis of variance variable overhead expenses comparing the total cost of a standard with the actual, because still any variance is unfavorable, this is due to flawed control of factory overhead costs at PG. Meritjan Kediri. KeyWords : Flexible Budget, Factory Overhead Cost